When and Where Was the Charter for Hilandar of Stephen Nemanjić Given? - Szefliński, Błażej (Balcanica Posnaniensia. Acta et studia, 2020)
The so-called Second Charter for Hilandar given by Stephen Nemanjić is one of the oldest Serbian documents that preserved to our times. It dates itself on 29th September, but without any year or indiction. Since the publishing of Aleksandar Solovjev's paper in 1925 it had been commonly accepted that the charter was given before 1202 because Stephen Nemanjić could name himself the son-in-law of emperor Alexios III Angelos only before the divorce with Eudokia Angelina. However, in 2010 Đorđe Bubalo has noticed that two later inscriptions – discovered after Solovjev's research – also emphasizes family connections between Nemanjić dynasty and Alexios, so the argument used by Solovjev cannot be held. Therefore, Bubalo has reanalysed the charter and suggested a new dating – to 1207-1208. However, one of his arguments – the Second Charter for Hilandar was used by Sava Nemanjić when writing the Life of Blessed Symeon – has lost its strength as such a relation between these texts is questioned in the newest research. Therefore, the objective of the hereby paper is to provide a new analysis of the Second Charter for Hilandar focused on when and (for the first time) where the document was given. The conclusion is that it happened after the hierophany of St Symeon – most probably on 29th September 1210 in the Hilandar monastery.